Design and Simulation of Compact Band-Pass Filter Using Stub Loaded Plasmonic Mim Waveguide - Vishwanath, M; Habibullakhan, Dr (International Journal of Engineering and Technology, 2018)
In this article, plasmonic band-pass filters (BPF) have been studied and numerically analyzed. This filter has been designed based on the two-stubs. Pass-band can be realized by appropriately adjusting the lengths and width of the resonator. Based on the ideal characteristics of the proposed two stubs BPF is allowing the band at THz frequencies. Multiple transmission zeros are generated to improve the selectivity of the filter. All simulated results have been studied using CST Microwave studio suite. Usually, the transmission effectiveness is revealed by the exact resonance condition, whichwill confirmalong with the numerical simulation or theoretical analysis.Â  This article delivers a promising application for plasmonic BPFsin addition to plasmonic integrated circuits (PICs).Â Â